"Messengers of Hope": A Boy With Autism, His Church, and the Special Olympics - Shrier, Paul (Journal of disability & religion, 2017)
Messengers of Hope is the story of Michael Leon, an adolescent on the autistic spectrum, his church, and the Special Olympics. It is a story of transformation. Michael's parents and family, Michael, and Montrose Church are all transformed through their participation in the Special Olympics. This article is primarily constructed by the author summarizing what he believes are the key elements of a 23-minute documentary movie. The author concludes with reflections, including thoughts from Brian Brock, John Swinton, and Amos Yong, as expressed in a separate, as-yet partially completed video project. Both video projects are intended to encourage churches and individuals to become involved with people with disabilities.